Inspiring change: The roles of women and their communities - Singapore Management University (Institutional Knowledge at Singapore Management University, 2011)
'Change' is a word often employed (and frequently abused) by politicians, industrialists, artists and leaders of various domains as a rallying call. Its effects can be profound on those discontented with the status quo and perhaps uninviting for those already contented with the way things are.